Review: Biomassa Sebagai Adsorbent untuk Pengolahan Logam Berat Pada Air Limbah Industri - Veranica, Veranica; Rahayu, Aster; Maryudi, Maryudi (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Industrial wastewater generally contains heavy metalssuch as lead, cadmium, arsenic, nickel, chromium and mercury. Contamination of water with these elements is very dangerous and will pollute the environment, so a suitable waste water treatment is required. This review aims to find out the efficient methods of handling industrial wastewater and the benefits of biomass. Many scientific methods are used in this regard, including adsorption, chemical precipitation, ion exchange, electrochemical treatment, membrane filtration, coagulation and flocculation. However, some of these techniques have drawbacks such aswill produce a large amount of metal sludge, making it difficult to recycle metal, and the formation of toxic sludge or other wastes. Of all these techniques, adsorption with adsorbent biomasshas been widely known because it is an economical, effective and environmentally friendly processing technique, so this method is suitable for treating industrial wastewater. The use of biomass as an adsorbent is intendedto help reduce dependence on fossil raw materials and greenhouse gas emissions that contribute to climate change.